Gun attitudes on campus: United and divided by safety needs. Issue 5 (3rd September 2018) - Shepperd, James A.; Pogge, Gabrielle; Losee, Joy E.; Lipsey, Nikolette P.; Redford, Liz
ABSTRACT: All people share a need for safety. Yet people's pursuit of safety can conflict when it comes to guns, with some people perceiving guns as a means to safety and others perceiving guns as a threat to safety. We examined this conflict on a U.S. college campus that prohibits guns. We distinguished between people ( N  = 11, 390) who (1) own a gun for protection, (2) own a gun exclusively for reasons other than protection (e.g., collecting, sports), and (3) do not own a gun. Protection owners felt less safe on campus and supported allowing guns on campus. They also reported that they and others would feel safer and that gun violence would decrease if they carried a gun on campus. Non-owners and non-protection owners felt the reverse. The findings suggest that protection concerns, rather than gun-ownership per se, account for diverging perceptions and attitudes about guns and gun control.